Air pollution in airports: ultrafine particles, solutions and successful cooperation (Copenhagen, 2012)
"Persons working close to exhaust from aircraft and/or diesel engines in airports are exposed to a complex mixture of potentially health damaging air pollution.The National Board of Industrial Injuries in Denmark has now recognised several cancer cases, most likely caused by air pollution in airports. The pollution is a serious and overseen work-related threat. The losers in the long run are both employees and employers. The main concern is related to ultrafine exhaust particles from aircraft and diesel engines. Ultrafine diesel particles are known to cause cancer, heart disease, blood clots, brain haemorrhage and serious airway diseases, thereby increasing the risk of serious work-related illness and premature death. However, not much is known about the toxicity of ultrafine aircraft particles. This booklet presents a new exhaustive study focusing on air pollution in Danish airports, pollution sources, employee exposure to ultrafine particles and actions to limit the pollution. The booklet is thereby state of the art regarding air pollution in airports. In addition, the booklet illustrates the success of solution-orientated cooperation involving Copenhagen Airport, companies operating in the airport and unions representing employees in the airport. The main aim of the booklet is to inspire decision makers and other key stakeholders in national and international organisations and in every airport to take action to reduce employee exposure to air pollution with ultrafine particles from aircraft and diesel engines."